EVALUATION OF DIFFERENT CROPPING SYSTEMS FOR THEIR PRODUCTIVITY AND SUSTAINABILITY IN MADHYA PRADESH - Singh, S P; Lal, S S (Potato Journal, 2013)
A field experiment was conducted during 2007–08 to 2009–10 at Gwalior to evaluate different cropping systems for their productivity and profitability. Cropping systems consisted of pearl millet, green gram, sesame and fallow during kharif and potato, wheat, mustard and fallow during rabi. Among kharif crops, pearl millet gave the highest wheat grain equivalent yield (WGEY). However, during rabi season highest WGEY was recorded with fallow–potato sequence. Maximum total WGEY (8.02 t/ha) of sequence was recorded with pearl millet–potato sequence, being 2.6% higher than green gram–potato and 12.3% higher than sesame–potato sequence. Highest sustainable value index (1.09) was recorded with green gram–potato sequence which was 13.8% higher than sesame–potato sequence. Highest net return (Rupees 59,749/ha) was recorded with pearl millet–wheat, production efficiency (Rupees 437/ha/day) with fallow–potato and B:C ratio (4.25) with fallow– mustard. Green gram–potato sequence was a viable proposition in the subtropical region of Madhya Pradesh which recorded highest sustaibability and almost equal WGEY with pearl millet–potato sequence. Adoption of more than one sequence at farm in rotation will diversify the cropping and reduce climatic aberrations.